Nutritional Content Analysis of Fortified Cookies from "Patin" bone flour waste and coconut dregs - Muhammad Aziz; Endang Fitriana; M. Risqi Sandi Pratama; Rahmi Rahmi (ALKIMIA, 2022)
Lack of intake can cause disturbances in health, growth, mental and other functions such as cognitive abilities, the immune system and reproduction. This problem can be overcome by carrying out food fortification, namely adding certain types of nutrients to food ingredients. Fortification can be made from food ingredients such as coconut dregs and Patin bones. These materials can be processed into flour as a source of nutritious food. Coconut dregs has a fairly high protein content and Patin bones have a high calcium content that the body needs for the growth process. This study aims to make nutritious food fortification by utilizing the local potential of Patin bones and coconut dregs, then an analysis of the moisture content, ash content, protein content, fat content, carbohydrate content and fiber content is carried out. The results of the analysis showed that Patin bone flour was obtained and coconut dregs flour contained water content, ash content, protein content, fat content, carbohydrate content and fiber content respectively were 3.02%, 6.29%, 6.21%, 20.89%, 64.08% and 6.58%. From the results of this analysis it can be concluded that Cookies with the addition of Patin bone flour and coconut dregs flour has good nutritional content. This research is expected to be used as one of the food innovations to support attempt fulfill the micronutrient nutrition needed for the human body.